Huseynov, Hasan - (:unkn) unknown (My University, 2026)
Hasan Ahmad oglu Huseynov was born on 7 September 1944 in the city of Jabrayil, Azerbaijan. In 1961, he graduated from the Jabrayil Secondary School named after Academician M. Mehdizade (formerly M. Gorky School). He subsequently earned his degree in Mechanical Engineering Technology, Metal-Cutting Machine Tools and Cutting Tools from the Azerbaijan Polytechnic Institute (AzPI) in 1967. Following his graduation, Professor Huseynov began his engineering career as a Senior Engineer at the Bunyad Sardarov Machine-Building Plant, upon assignment by AzPI. Between 1967 and 1968, he completed his compulsory military service in the Soviet Army. From 1968 to 1984, he worked at the All-Union Scientific Research and Design Technological Institute of Mechanical Engineering, where he served successively as Senior Engineer and Lead Engineer. In 1974, he entered the postgraduate (aspirantura) program at Azerbaijan Polytechnic Institute. He successfully defended his Candidate of Sciences (PhD equivalent) dissertation in 1978 at the Gubkin Moscow Institute of Oil and Gas, receiving the academic degree of Candidate of Technical Sciences. Since 1978, Professor Huseynov has pursued his academic career at Azerbaijan Polytechnic Institute (now Azerbaijan Technical University), serving successively as Junior Researcher, Assistant Lecturer, Senior Lecturer, Associate Professor, and Professor. During the 1984–1985 academic year, he completed a ten-month intensive French language program at the Maurice Thorez Moscow State Institute of Foreign Languages. Between 1984 and 1987, he served as a Professor at the University of Madagascar. In 1990, Professor Huseynov was elected Head of the Department of Computer-Aided Systems in Mechanical Engineering (ALS). He defended his Doctor of Sciences (DSc) dissertation in 1995 at the Moscow State Technological University "STANKIN". In 1996, he was elected a Full Member (Academician) of the Russian Academy of Quality Problems and was awarded the academic title of Professor. Professor Huseynov is the author of more than 150 scientific and methodological publications, including four inventions, three monographs, numerous university textbooks, and teaching manuals. Four of his textbooks were published in French in the Democratic Republic of Madagascar. He has supervised the successful completion of six Candidate of Technical Sciences (PhD equivalent) dissertations. In 2005, on the initiative and with the active participation of Professor Huseynov, Azerbaijan Technical University organized the International Scientific and Technical Conference on "Modern Problems of Mechanical Engineering and Instrument Engineering", dedicated to the 55th anniversary of the University. Professor Huseynov has published a number of substantial analytical articles in the national newspapers "Respublika" and "Azərbaycan", addressing strategic issues of higher education and industrial development. His publications have focused on the implementation of the Bologna Process, challenges facing the mechanical engineering sector, mechanisms for implementing the State Strategy for the Development of Education, the introduction of a differentiated salary system, and other contemporary issues of national importance. Under his scientific leadership, major outcomes of two state-funded research projects have been officially registered by the state and recommended for implementation across various sectors of Azerbaijan's industry. Professor Huseynov has established extensive international academic collaborations. Through the DAAD programme and the TEMPUS initiative, he has undertaken numerous long-term research visits to leading European universities. He currently serves as the coordinator of regional TEMPUS and Erasmus+ projects. Many of his former students are currently employed as academic staff at universities in Germany. Professor Huseynov is a member of the Faculty Council of the Faculty of Technological Machines, the Academic Council of Azerbaijan Technical University, the Scientific and Methodological Council, and the Dissertation Council. He also serves as Chair of the Scientific Seminar operating under the Dissertation Council. In recognition of his outstanding contributions to science, higher education, and engineering, Professor Hasan Huseynov was awarded the honorary title of Honoured Scientist of the Republic of Azerbaijan by a decree of the President of the Republic of Azerbaijan.
Keywords: Computer Science; Engineering; Automation & Control Systems